Alkyl Chain Engineering of Solution-Processable Star-Shaped Molecules for High-Performance Organic Solar Cells - Min, Jie; Luponosov, Yuriy N.; Gerl, Andreas; Polinskaya, Marina S.; Peregudova, Svetlana M.; Dmitryakov, Petr V.; Bakirov, Artem V.; Shcherbina, Maxim A.; Chvalun, Sergei N.; Grigorian, Souren; Kaush-Busies, Nina; Ponomarenko, Sergei A.; et al. (Advanced Energy Materials, 2014)
The impact of alkyl side-chain substituents on conjugated polymers on the photovoltaic properties of bulk heterojunction (BHJ) solar cells has been studied extensively, but their impact on small molecules has not received adequate attention. To reveal the effect of side chains, a series of star-shaped molecules based on a triphenylamine (TPA) core, bithiophene, and dicyanovinyl units derivatized with various alkyl end-capping groups of methyl, ethyl, hexyl and dodecyl is synthesiyed and studied to comprehensively investigate structure-properties relationships. UV-vis absorption and cyclic voltammetry data show that variations of alkyl chain length have little infl uence on the absorption and highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) levels. However, these seemingly negligible changes have a pronounced impact on the morphology of BHJ thin films as well as their charge carrier separation and transportation, which in turn influences the photovoltaic properties of these small-molecule-based BHJ devices. Solution-processed organic solar cells (OSCs) based on the small molecule with the shortest methyl end groups exhibit high short circuit current (Jsc) and fill factor (FF), with an efficiency as high as 4.76% without any post-treatments; these are among the highest reported for solution-processed OSCs based on star-shaped molecules.
Keywords: Engineering controlled terms: Charge carriers; Heterojunctions; Molecules; Solar cells; Stars Carrier separation; Highest occupied molecular orbital; Lowest unoccupied molecular orbital; Power conversion efficiencies; Side-chains; Star-shaped molecules; Structure property relationships; Structure-properties relationships Engineering main heading: Synthesis (chemical)